Menjunjung Kebersamaan Dalam Perbedaan: Studi Moderasi Beragama di Indonesia Perspektif Tafsir Maudhu’i - Nasher, Abdurrahman; Malihah, Nadia Rosikhoh; Fauziah, Salma; Luthfiyyah, Nayla Desiyana; Santoso, Muhammad Iqbal Firdaus; Saputra, Muhammad Ragil; Fauzi, Asep Muhammad; Muhyi, Asep Abdul; Chodijah, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research article aims to understand religious moderation in the perspective of the interpretation of the Qur’an thematically/maudhu’I from various classical, modern, and contemporary interpretation books and to find out the existence of religious moderation in Indonesia. The method used is qualitative research by taking data from literature studies from books, scriptures, and journals that have a high H-index and citation rate based on the Publish or Perish application. In this study, it was found that there are five verses of the Qur’an that contain words that are in line with moderation, namely wasathan, wustha, awsath, and wasathan which have the meaning of middle, fair, good, and most important. The real contribution that can be made from this research is as a reference in implementing religious moderation from the interpretation perspective and can be socialized to the Indonesian people. This research focuses on the realm of interpretation related to religious moderation and to add to the intellectual treasury of Islam in facing the challenges of religious life and religiosity to welcome tolerance and peace among religious adherents.